A brief history of inflation in China - Zheng, Qidong (Economic history in China series., 2013)
The titles in the 'Economic History in China' series investigate the roots of China's economic successes and advancements. This book examines the history and effect of inflation, which remains a commonly misunderstood aspect of China's overall economic success and fiscal control.